Complex Interplay Among Nuclear Receptor Ligands, Cytosine Methylation, and the Metabolome in Driving Tris(1,3-Dichloro-2-Propyl) Phosphate-Induced Epiboly Defects in Zebrafish - Dasgupta, Subham (Environ Sci Technol, 2019)
Tris(1,3-dichloro-2-propyl) phosphate (TDCIPP) is a high-production volume organophosphate flame retardant (OPFR) that induces epiboly defects during zebrafish embryogenesis, leading to disruption of dorsoventral patterning. Therefore, the objectives of this study were to 1) identify potential mechanisms involved in TDCIPP-induced epiboly defects and 2) determine whether co-exposure to triphenyl phosphate (TPHP) – an OPFR commonly detected with TDCIPP – enhances or mitigates epiboly defects. While TDCIPP-induced epiboly defects were not associated with adverse impacts on cytoskeletal protein abundance in situ, co-exposure of embryos to TPHP partially blocked TDCIPP-induced epiboly defects. As nuclear receptors are targets for both TPHP and TDCIPP, we exposed embryos to TDCIPP in the presence or absence of 69 nuclear receptor ligands and, similar to TPHP, found that ciglitazone (a peroxisome proliferator-activated receptor γ agonist) and 17β-estradiol (E2; an estrogen receptor α agonist) nearly abolished TDCIPP-induced epiboly defects. Moreover, E2 and ciglitazone mitigated TDCIPP-induced effects on CpG hypomethylation within target loci prior to epiboly, and ciglitazone altered TDCIPP-induced effects on the abundance of two polar metabolites (acetylcarnitine and CDP-choline) during epiboly. Overall, our results point to a complex interplay among nuclear receptor ligands, cytosine methylation, and the metabolome in both the induction and mitigation of epiboly defects induced by TDCIPP.